2010
DOI: 10.1042/bj20091234
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis thaliana NAC transcription factor family: structure–function relationships and determinants of ANAC019 stress signalling

Abstract: TFs (transcription factors) are modular proteins minimally containing a DBD (DNA-binding domain) and a TRD (transcription regulatory domain). NAC [for NAM (no apical meristem), ATAF, CUC (cup-shaped cotyledon)] proteins comprise one of the largest plant TF families. They are key regulators of stress perception and developmental programmes, and most share an N-terminal NAC domain. On the basis of analyses of gene expression data and the phylogeny of Arabidopsis thaliana NAC TFs we systematically decipher struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
406
1
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 362 publications
(424 citation statements)
references
References 48 publications
11
406
1
6
Order By: Relevance
“…1B). 9 However, conserved ID patterns were reveled for several NAC subgroups ( Fig. 2), in accordance with the suggestion that disorder patterns are constrained compared to sequences.…”
supporting
confidence: 56%
See 4 more Smart Citations
“…1B). 9 However, conserved ID patterns were reveled for several NAC subgroups ( Fig. 2), in accordance with the suggestion that disorder patterns are constrained compared to sequences.…”
supporting
confidence: 56%
“…1) with interspersed conserved sequence motifs. 9 Our recent work 10 characterizing NAC ID suggested that the large disordered TRD of ANAC0046 forms an entropic chain which is well-suited for molecular fishing of e.g., RCD1 (Fig. 1A).…”
mentioning
confidence: 99%
See 3 more Smart Citations